Effects of Helicobacter pylori and liver cirrhosis on gastric mucosal hexosamine concentrations - Murat ARABACI,; Tankut KÖSEOĞLU,; Yücel ÜSTÜNDAĞ,; Kamer ASLAMİRZA,; Erdal ESKİOĞLU, (Turkish Journal of Gastroenterology, 2019)
-